A low-profile high-isolation endfire MIMO antenna based on spoof surface plasmon polaritons for X-band applications - Jatav R.; Mali R.; Rathore P.S.; Meshram M.K. (My University, 2025)
This work proposes a three-port, low-profile, coplanar endfire multiple-input-multiple-output (MIMO) antenna based on spoof surface plasmon polaritons (SSPPs). The proposed antenna comprises a coplanar waveguide (CPW)-fed SSPPs transmission line (TL). A transition to transform the CPW quasi-TEM mode to the SSPPs mode. The radiator section with asymmetric discontinuities converts the bounded SSPPs waves into radiating waves. The proposed MIMO antenna exploits the inherent feature of high isolation in the SSPPs TL due to its strong field confinement competency. Wider beamwidths for ample azimuth and elevation coverage with a stable pattern in the endfire direction are achieved in the 9.52–11.23 GHz operating band. In the operating band, the MIMO antenna has an average realized gain of 6 dBi. Mainly, it has high isolation below -35 dB (measured) in the operating range, a maximum envelope correlation coefficient (ECC) of 1.5 × 10−3, and a total active reflection coefficient (TARC) value below 0.3. The measured results are closely matched with the simulated ones in terms of S-parameters, radiation pattern, ECC, TARC, and CCL. © 2024